1991
DOI: 10.1177/104063879100300115
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Cutaneous and Visceral Infection in a Rottweiler Dog Associated with a Sarcocystis-Like Protozoon

Abstract: A 10-month-old male Rottweiler dog from Ottawa, Illinois, had persistent diarrhea for 2 months. After the diarrhea stopped, the dog developed multiple cutaneous abscesses all over its body, particularly in the hind limbs. The limbs were swollen, hot, and painful. A skin biopsy was fixed in 10% formalin solution. The dog died, and the carcass was frozen until necropsy. No other history was available.Portions of liver, unspecified lymph node, lungs, kidney, and skin from the frozen-thawed carcass were fixed in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 2 publications
0
14
0
Order By: Relevance
“…The type of host reactions in S. canis and conventional species of Sarcocystis also differs. Sarcocystis canis and S. neurona typically cause necrosis, whereas lesions in conventional Sarcocystis species are generally inflammatory 5,6 The lesions in the liver of this chinchilla were identical to those reported in a Rottweiler dog. 2 Sarcocystis species have a 2-host life cycle.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…The type of host reactions in S. canis and conventional species of Sarcocystis also differs. Sarcocystis canis and S. neurona typically cause necrosis, whereas lesions in conventional Sarcocystis species are generally inflammatory 5,6 The lesions in the liver of this chinchilla were identical to those reported in a Rottweiler dog. 2 Sarcocystis species have a 2-host life cycle.…”
mentioning
confidence: 79%
“…The reagents and controls were the same as used previously. 6,14 Histologically, the liver contained random, variably sized In the article "Experimental rayless goldenrod (Isocoma pluriflora) toxicosis in goats" by Bryan L. Stegelmeier et al, the published mean body weight and the means and statistics of serum biochemistries were carried out on groups of 4 animals, not 3, as described in the Material and Methods section. The additional animal in each group was part of an auxiliary physiologic study and though the animals were dosed and treated the same, they were not necropsied and were not included in the histologic study.…”
mentioning
confidence: 99%
“…Hosts in which mature sarcocysts have been demonstrated are the intermediate hosts. Laboratory-raised opossums excreted sporocysts after feeding naturally infected skunk, raccoon, sea otter or armadillo muscle (Cheadle et al, 2001c; Cheadle et al, 2001d; Tanhauser et al, 2001; Dubey et al, Dubey et al, 2001b, Dubey et al, 2001c), indicating that they are proven intermediate hosts of S. neurona . Mansfield et al (2008) reported brown-headed cowbirds as intermediate host for S. neurona but this finding needs confirmation.…”
Section: Biologymentioning
confidence: 99%
“…Giemsa stain. ( A ) Smear from a pustular dermal ulcer from a Rottweiler dog reported by Dubey et al (1991b). Note several intensely stained schizonts (arrows) among leukocytes and RBC.…”
Section: Figurementioning
confidence: 99%
“…Confirmed cases of dermatitis have been associated with Caryospora sp. 6 and S. canis 14 23 Amastigotes containing kinetoplasts are pathognomonic for Leishmania. Toxoplasma gondii can infect virtually all body tissues; however, there are no reported cases of cutaneous toxoplasmosis in dogs.…”
mentioning
confidence: 99%